Clinical Cases in Heart Failure (Clinical Cases in Cardiology,, 2018)
This concise practical guide is designed to facilitate the clinical decision-making process by reviewing a number of cases and defining the various diagnostic and management decisions open to clinicians. It is well illustrated and diverse in scope, enabling the reader to obtain relevant clinical information regarding both standard and unusual cases in heart failure in a rapid, easy to digest format. Clinical cases are a key component in modern medical education, assisting the trainee or recertifying clinician to work through unusual cases using best practice techniques. Cardiology is a key discipline in this regard and is a highly visual subject requiring the reader to describe often very subtle differences in the presentation of patients and define accurately the diagnostic and management criteria on which to base their clinical decision-making. This title therefore provides valuable assistance to trainees and clinicians alike in evaluating pati ents and defining an appropriate procedure for each case covered.